Endovascular Debulking of Human Carotid Plaques by Using an Excimer Laser Combined With Balloon Angioplasty: An ex vivo Study - Yang, Kai; Tan, Jinyun; Deng, Ying; Shi, Weihao; Yu, Bo (Frontiers in Cardiovascular Medicine, 2021)
Abstract Purpose: To evaluate the safety and effectiveness of applying excimer laser in debulking human carotid atherosclerotic plaques by investigating distal debris, plaque luminal gain and micromorphology of plaque surface. Methods: 18 plaque samples obtained from carotid endarterectomy (CEA) were randomly allocated to excimer laser ablation (45 mj/mm^2, 25Hz) alone group (Group 1), balloon angioplasty (8 atm) alone group (Group 2), and excimer laser ablation combined with balloon angioplasty group (Group 3), respectively. Collected particles were performed with hematoxylin-eosin staining and Movat’s pentachrome staining to quantify the size and compositions of debris. Superficial micromorphological structure of plaque lumen surface after device treatments was observed by scanning electron microscope. Micro-CT, tissue sections and pathological stainings were applied to treated plaques. Plaque lumen and artery lumen were 3-dimensionally reconstructed by clinical computed tomography angiography and Micro-CT images. Lumen enlargement was set as the main measurement of effectiveness. Results: The Group 3 produced the highest luminal gain (5.40 ± 4.51 mm²), while the other two groups were 4.05 ± 3.20 mm² and 3.77 ± 2.55 mm². Both devices brought disruptions to plaque lumen surface. Laser ablation exposed the fibers under the endothelium and balloon angioplasty cracked the surface. Mean amount of each group was 3611 ± 1475.4 (Group 1), 2828 ± 1266.7 (Group 2), 4400 ± 2567.9 (Group 3), respectively. More than 90 % of distal debris was smaller than 10 μm. The Group 2 produced the most debris with Feret ≥ 40 μm, the Group 1 was the least. There was little difference in the content of collagen & reticular fiber of debris in each group, but big difference was observed in the content of fibrin and mucin. Conclusion: Excimer laser ablation could significantly increase luminal gain of carotid plaque with high stenosis. Excimer laser combined with balloon angioplasty achieved the highest lumen enlargement. Our result also suggested that embolic protection strategy need to be renewed for the application of plaque debulking device in the future.